Local Strategies for Sustainable Dragon Fruit: A Mixed-Method SWOT Analysis of Agribusiness Development in Sinjai - A. Nurazizah; Fadilah Nurdin; Megawati (FAKULTAS PERTANIAN UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2025)
This study aims to formulate alternative strategies and determine the priority strategies that can be implemented in developing dragon fruit farming. The type of research used in this study is a mix method, namely a combination of quantitative and qualitative research methods, taking the case of the Dragon Fruit Farming Group in Sukamaju Village, Tellulimpoe District, Sinjai Regency. Respondents in this study used a census of 20 dragon fruit farmers. The results of the study indicate that the IFAS value of 4.85 and the EFAS value of 5.10, this farm still occupies a strategic position for continued development because the opportunity score is more dominant than the threat score. In the SWOT diagram, the position of the development strategy is located in quadrant 1 or referred to as an aggressive strategy. The priority strategy that can be implemented is to improve the quality of dragon fruit by utilizing developments in agricultural technology to meet the increasing demand for products according to consumer tastes and maintain the sustainability of dragon fruit marketing